Ad Hoc Network Hybrid Management Protocol Based on Genetic Classifiers - Garzia, Fabio; Perna, Cristina; Cusani, Roberto (Scientific Research Publishing, 2010)
The purpose of this paper is to solve the problem of Ad Hoc network routing protocol using a Genetic Algorithm based approach. In particular, the greater reliability and efficiency, in term of duration of communication paths, due to the introduction of Genetic Classifier is demonstrated.
Keywords: Ad Hoc Networks; Genetic Algorithms; Genetic Classifier Systems; Routing Protocols; Rule-Based Processing